Understanding the effects of the presence of others in the service environment: A literature review - Kathrin Albrecht (jbm - Journal of Business Market Management, 2016)
Sharing the same service environment leads to direct and indirect interactions between customers that can either enhance or damage a customer's service experience. Especially in situations where customers are observing complaint situations of others, negative effects can be transmitted to the observing party, thus posing a considerable threat to the service provider. Although many research studies have examined the presence of other customers in a service context, a literature review systemizing both theoretical and empirical findings is still lacking. Through the current literature analysis three contextual factors have evolved that affect customerto-customer interactions during service encounters in the service environment, i.e. customer-related factors, firm-related factors and encounter-related factors. Finally, four avenues of future research are exposed with regard to the contextual factors. Moreover, this article helps managers to carefully design their customer experience initiatives with regard to socially present other customers in the service environment.
urn:nbn:de:0114-jbm-v9i1.1534
Keywords: 650; Other customers; Service Environment; Customer interactions